Analysis of Digital Marketing Strategy in Branding Islamic Boarding Schools in Daarut Tauhiid Bandung.docx - Zahrotul Munawwaroh; Puji Rahayu (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This study examines various digital marketing strategies that can improve branding efforts in pesantren. The research method uses a descriptive qualitative approach to analyze digital marketing strategies in improving branding in pesantren. The findings show that integrating traditional values with modern digital innovations can significantly increase the effectiveness of branding efforts in pesantren. In addition, community engagement through various outreach programs increases the social impact of these institutions and strengthens their position as significant contributors to local economic development. The discussion highlighted five key strategies: strengthening a unique identity, leveraging digital media, developing flagship programs, building strategic partnerships, and engaging the community in social initiatives. Each strategy is critical to strengthening the educational mission of pesantren while fostering a deeper relationship with the surrounding community. This study concludes that pesantren equipped with a solid digital marketing approach and a clear strategic direction can improve their branding and educational effectiveness. Future research is recommended to investigate the specific impact of community empowerment programs and the utilization of digital technology on the quality of education in pesantren, as well as longitudinal studies to assess the long-term success of the strategic partnerships formed by these institutions.